“Girls should be ready for anything”: time, learning and aspiration among hostel girls in Lahore - Arif, YR (2023)
This thesis explores the lives of a group of young, middle-class women living in a privately-run girls’ hostel in Lahore. The key question that this thesis seeks to address is the meaning of this stage in the lives of young women. A temporary period of accommodation in an urban hostel while studying is increasingly conceptualised as part of the life course for middle-class young women, bracketed by childhood in the natal household and married, virilocal adulthood. What does it mean to move to the city alone as a young Pakistani woman, and how do these women understand the experience of being a ‘hostellite’?